2008
DOI: 10.1053/j.gastro.2008.02.063
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Activation by Hepatitis C Core Protein Is Reversed by Ethanol-Induced Oxidative Stress

Abstract: Background and Aims-The proteasome is a major cellular proteinase. Its activity is modulated by cellular oxidants. Hepatitis C core protein and ethanol exposure both cause enhanced oxidant generation. The aim was to investigate whether core protein, by its ability to generate oxidants, alters proteasome activity and whether these alterations are further affected byethanol exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 37 publications
3
51
0
Order By: Relevance
“…Previous studies suggested that ethanol does not alter phagocytosis or pinocytosis of exogenous antigens by DCs (1). However, Osna et al reported that ethanol inhibited proteasomal degradation of peptides and thus reduced their presentation by MHCI molecules in hepatocytes (26). To resolve these discordant observations and to further explore the possible inhibitory influence of ethanol on the processing of exogenous antigens taken up through an endocytic process as a potential mechanism for depressed Tcell activation, we compared the kinetics of endocytosed OVA protein degradation by DCs isolated from control and ethanolfed BALB/c mice.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies suggested that ethanol does not alter phagocytosis or pinocytosis of exogenous antigens by DCs (1). However, Osna et al reported that ethanol inhibited proteasomal degradation of peptides and thus reduced their presentation by MHCI molecules in hepatocytes (26). To resolve these discordant observations and to further explore the possible inhibitory influence of ethanol on the processing of exogenous antigens taken up through an endocytic process as a potential mechanism for depressed Tcell activation, we compared the kinetics of endocytosed OVA protein degradation by DCs isolated from control and ethanolfed BALB/c mice.…”
Section: Resultsmentioning
confidence: 95%
“…There is a repertoire of distinct DC subsets (14) that are specialized to take up, process, and present exogenous and endogenous antigens to CD4 ϩ T cells via major histocompatibility complex class II (MHCII) molecules and to CD8 ϩ T cells by MHCI molecules, respectively (29). Recently, ethanol was shown to inhibit MHCI presentation of peptides by interfering with the proteasomal degradation of antigens in hepatocellular carcinoma cells in a CYP2E1-dependent manner (25,26). However, the influence of ethanol on antigen processing and presentation by DCs, along with the formation of the peptide-MHCII complex on the cell surface as it relates to impaired T-cell activation, has not been investigated previously.…”
mentioning
confidence: 99%
“…This proteasome activation event is, however, reversed after ethanol exposure which considerably reduces proteasome function due to the induction of high oxidative stress [66] . Ethanol-elicited suppression of the proteasome in the liver ultimately results in a reduced generation of antigenic peptides and reduced MHC class Ⅰ-restricted antigen presentation on hepatocytes [68] .…”
Section: Mhc Class ⅰ-Restricted Hcv Antigen Presentation and The Effementioning
confidence: 98%
“…In Huh-7 cells co-expressing the HCV core protein and CYP2E1, the core protein slightly enhances 20S proteasome activity through a direct interaction and via the induction of low CYP2E1-dependent oxidative stress [66,67] . This proteasome activation event is, however, reversed after ethanol exposure which considerably reduces proteasome function due to the induction of high oxidative stress [66] .…”
Section: Mhc Class ⅰ-Restricted Hcv Antigen Presentation and The Effementioning
confidence: 99%
“…In addition, HCV proteins affect the enzyme activity: core protein regulate proteasome activity via protein-protein interactions and oxidative stress [8], while NS3 protein blocks the activity of IFNstimulated immunoproteasome (LMP7 subunit) that trims the peptides for antigen presentation in the context of MHC class I to cytotoxic T-lymphocytes [9].…”
Section: Hcv and Upsmentioning
confidence: 99%